2024
DOI: 10.1063/5.0179201
|View full text |Cite
|
Sign up to set email alerts
|

Particle clogging mechanisms in hyporheic exchange with coupled lattice Boltzmann discrete element simulations

Xudong Zhang,
Dewei Du,
Teng Man
et al.

Abstract: The clogging of a stream bed has a significant impact on the exchange of water between a river and groundwater, known as hyporheic exchange. Clogging issues in orifices influenced by fluid flow have long been a concern, particularly in understanding clogging mechanisms and particle dynamics. This study focuses on investigating the behavior of poly-dispersed particle systems in the Shanghai soft soil using a coupled lattice Boltzmann method and a discrete element method (LBM-DEM). A particle-orifice model was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Geothermal resources are a stable, reliable, green and low-carbon renewable resource, and compared with fossil fuels, geothermal energy is a valuable resource with large reserves and is environmentally friendly and sustainable [1][2][3]. Since 2010, geothermal energy in China entered into a period of rapid development for the use of heating and cooling buildings and for the generation of electricity [4].…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…Geothermal resources are a stable, reliable, green and low-carbon renewable resource, and compared with fossil fuels, geothermal energy is a valuable resource with large reserves and is environmentally friendly and sustainable [1][2][3]. Since 2010, geothermal energy in China entered into a period of rapid development for the use of heating and cooling buildings and for the generation of electricity [4].…”
Section: Introduction Backgroundmentioning
confidence: 99%
“…Furthermore, it is important to consider the impact of water-related disasters, such as floods and tidal actions, on the stability and safety of high-pile foundations. Particularly in riverine and marine environments, variations in water flow intensity and direction can cause soil erosion around the pile foundations, thereby increasing the risk of structural failure [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The results of laboratory model testing showed that when the fine particle content reached about 28%, the slag debris flow can occur under weak climatic-hydrological conditions [17]; it was also observed in a similar model that the collapse of an accumulation body made it easy to produce slide-blockage-collapse-type debris flows at this level of fine particle content, and required the minimum amount of water [7,18]. The process of particle migration and deposition was established using a numerical model, and the instability failure and possible harm of the accumulation body were analyzed and calculated [19][20][21][22][23]. In order to determine the influence mechanism of fine particle migration, deposition and clogging more effectively on the instability of the accumulation slope, Wang et al [24], through the method of model testing, found that fine particles would migrate with rainwater, block the fine pores and reduce the permeability of soil, eventually leading to failure or collapse.…”
Section: Introductionmentioning
confidence: 99%